Anaerobic co-digestion of oil-extracted spent coffee grounds with various wastes: Experimental and kinetic modeling studies. (February 2021) - Atelge, M.R.; Atabani, A.E.; Abut, Serdar; Kaya, M.; Eskicioglu, Cigdem; Semaan, Georgeio; Lee, Changsoo; Yildiz, Y.Ş.; Unalan, S.; Mohanasundaram, R.; Duman, F.; Kumar, Gopalakrishnan
Graphical abstract: Highlights: The extraction of oil was used for SCGs as a pretreatment method for AD. DSCGs outperform SCGs according to BMP as well as TS and VS removal. Enhancement of CH4 yield was obtained when the percentage of DSCG was increased. Abstract: The effect of oil extraction from spent coffee grounds as a pre-treatment strategy prior to anaerobic digestion besides assessing the feasibility of defatted spent coffee grounds co-digestion with spent tea waste, glycerin, and macroalgae were examined. Mesophilic BMP tests were performed using defatted spent coffee grounds alongside four co-substrates in the ratio of 25, 50, and 75%, respectively. The highest methane yield was obtained with the mono-digestion of defatted spent coffee grounds with 336 ± 7 mL CH4 /g VS and the yield increased with the increase in the mass ratio of defatted spent coffee grounds during co-digestion. Moreover, defatted spent coffee grounds showed the highest VS and TS removal at 35.5% and 32.1%, respectively and decreased thereafter. Finally, a linear regression model for the interaction effects between substrates was demonstrated and showed that distinctly mixing defatted spent coffee grounds, spent coffee grounds, and spent tea waste outperforms other triple mixed substrates.